Kejadian Perdarahan Postpartum dengan Paritas dan Anemia - Lisna Ferta Sari (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2018)
According to Indonesia Health Profile in 2014, four causes of maternal mortality were bleeding 30.3%, hypertension 27.1%, infection 7.3%, and others did not cause directly such as cancer, kidney, hearth, or other diseases 35.3%). Bleeding after labor, or postpartum bleeding was a more general cause of perinatal and maternal mortality in a developed country and it caused maternal morbidity in all over the world. Postpartum bleeding was the loss of more than 500 ml of blood after per vaginam labor, or 1000 ml of blood after Caesar section. The objective of the research was to know the relationships between parity and anemia with postpartum bleeding in RSUD year 2017. The study used an analytical survey method of a cross-sectional approach. The population in the study was all mothers giving birth in RSUD Kota Prabumulih from January 1st to December 31st, 2017 about 1385 mothers giving birth. The result of the research based on univariate analysis, it was known that from 310 respondents, 128 (41.3%) respondents experienced postpartum bleeding, and those were not about 182 (58.7%) respondents. 157 respondents (50.6%) had risky parity and 153 respondents (49.4%) did not. 114 respondents (36.8%) experienced anemia and 196 respondents (63.2%) did not. The result of bivariate analysis was gotten that there was a meaningful relationship between parity (p-value = 0.001) and anemia (p-value = 0.001).with postpartum bleeding. The conclusion of the research was there was a meaningful relationship between parity and anemia with postpartum bleeding in RSUD Kota Prabumulih year 2017.